2005
DOI: 10.1213/01.ane.0000147667.06156.df
|View full text |Cite
|
Sign up to set email alerts
|

Recovery After Anesthesia for Short Pediatric Oncology Procedures: Propofol and Remifentanil Compared with Propofol, Nitrous Oxide, and Sevoflurane

Abstract: Anesthesia techniques in children undergoing short painful oncology procedures should allow rapid recovery without side effects. We compared the recovery characteristics of two anesthetic techniques: propofol with sevoflurane and nitrous oxide and a total IV technique using propofol and remifentanil. Twenty-one children, undergoing two similar painful procedures within 2 wk were studied in a single-blind manner within patient comparison. The order of the techniques was randomized. Propofol and remifentanil inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…The pharmacodynamic properties of propofol include early return of alertness and decreased postanesthesia nausea and vomiting. Therefore, IV remifentanil combined with propofol seems to be a better anesthetic technique [2].…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacodynamic properties of propofol include early return of alertness and decreased postanesthesia nausea and vomiting. Therefore, IV remifentanil combined with propofol seems to be a better anesthetic technique [2].…”
Section: Discussionmentioning
confidence: 99%
“…Candiotti et al [13] reported that less fentanyl was required for sedation with dexmedetomidine (84.8 vs. 144.4 g for the dexmedetomidine and placebo groups, respectively) compared with midazolam (placebo) for all surgical subtypes. Combination of ketamine and dexmedetomidine has several advantages: the decreased dosages of both sedative agents needed for clinical sedation decreased hemodynamic side effects [14] ; intravenous injection enables quicker recovery [15] and causes less air pollution in the operating room than inhaled anesthetics [16] . Mahmoud et al [17] reported that addition of dexmedetomidine decreased the dose of ketamine and thereby its related side effects.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of propofol and remifentanil, delivered intravenously, over conventional volatile anesthetic agents used in children are quicker recovery (1), reduced nausea and vomiting (2), decreased postoperative delirium (3) and less environmental pollution (4). Organ specific effects, such as reduced airway reactivity, improved postoperative ciliary function (5), maintained cerebral vascular reactivity (6), and preserved middle ear pressure (7) are significant advantages in specific clinical situations.…”
Section: Introductionmentioning
confidence: 99%